Higher productivity on smaller farms - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Adoption of hybrid maize in Zambia: effects of gender roles in agriculture, food consumption and nutrition by S K Kumar, IFPRI Research Report 100